Reliable Control for Uncertain Singular Systems with Randomly Occurring Time-Varying Delay and Actuator Faults - Yu-Lin Li; Lin-Sheng Li; Zhi-Cheng Zhao; Jing-Gang Zhang (Abstract and Applied Analysis)
The problem of reliable control is investigated for uncertain continuous singular systems with randomly occurring time-varying delay and actuator faults in this work. The delay occurs in a random way, and such randomly occurring delay obeys certain mutually uncorrelated Bernoulli distributed white noise sequences. The uncertainties under consideration are norm-bounded, and may vary with time. Then, with the constructed Lyapunov function, a sufficient condition is given to ensure the unforced system is mean-square exponentially stable and the corresponding controller can be derived from such condition, and the actuator faults problem is guaranteed. A numerical example is provided to show the effectiveness of the methods.